STAGNANT WAGES AND THE SQUEEZE ON LIVING STANDARDS IN MALAYSIA: CONCEPTUAL INSIGHTS - Siew Huay, Chong; Jamaludin, Salwaty; Ya’acob, Fatin Farazh; Kurniasih, Lulus; Alpandi, Rabiatul Munirah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
This conceptual paper investigates the persistent challenge of wage stagnation in Malaysia's rapidly evolving economy. Despite achieving remarkable economic growth and structural transformation since the 1980s, Malaysia faces a critical disconnect between productivity gains and real wage growth. Our analysis reveals systemic barriers to equitable income distribution. Building on existing theory and evidence, we develop an integrated conceptual model of wage determination in Malaysia's context. The findings highlight the dual impact of Malaysia's heavy reliance on low-skilled foreign workers and its weak collective bargaining systems in suppressing wage growth, particularly in labor-intensive sectors. The paper further reveals how current economic policies favoring capital-intensive development have inadvertently created systemic barriers to equitable income distribution. Building on existing theoretical frameworks and empirical evidence, this study proposes an integrated conceptual model that captures the complex dynamics of wage determination in Malaysia's unique economic context and necessitate urgent policy reform—targeting skill mismatches, strengthening wage-setting mechanisms, and rebalancing capital-labor power dynamics—to break the stagnation cycle.